Isolation of Acinetobacter baumannii from patient and hospital environment: analyzing their antibiotic resistance, serum resistance & biofilm formation - Jinnah, Mst. Maskera; Fatema, Kaniz (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2024.